DYNAMIC TEACHING MODELS TO ENGLISH INSTRUCTION IN THE MILLENNIUM CLASSROOM - Wayan Maba; Ida Ayu Made Sri Widiastuti (International Journal of Social Science, 2024)
This literature study aims to analyze dynamic learning models. Analysis carried out on learning models and their implementation in conditioned classrooms. The method used for this research is descriptive qualitative. This research uses a qualitative research design where the data is analyzed using the deep argumentation method, and the analysis is presented descriptively. The required data was collected through case studies from various references available in national and international journals. The collected data was analyzed comprehensively and analytically to obtain findings. This research showed that several innovative learning models can be used and are suitable for learning English in the millennium era. This research implies that the teaching model chosen is based on the currently developed language approach. Teachers must use appropriate teaching models to improve their students' competence